The importance of dilapidation survey before the commencement of construction work in Malaysia / Nurul Afiqah Mohammad Batni - Mohammad Batni, Nurul Afiqah (Faculty of Architecture, Planning and Surveying, 2015)
This research will focus on the importance of dilapidation survey before the commencement of construction work in Malaysia. Dilapidation surveys are performed by a building surveyor to assess the pre-construction condition of a property including the internal and external condition, as well adjacent structures. Any existing defects within the structure are then recorded in a detailed report which may include cracks, distortion, leakages, settlement, and others. This research has 6 Chapters that will discuss the overall research. In Chapter 1, the writer will start to introduce the main problem and highlight the issue of the topic. The problem that was highlighted in this research is lack of public awareness on how important of dilapidation survey before the commencement of construction work. This chapter wills also provide the overview of the aim and objectives, methodology, scope and limitation etc. Chapter 2 will indicates the comprehensive review of the research. It is general survey of the related research literature. It also indicates what researcher already knows and do not know yet about this topic. The key study for this chapter is widely cited by others in the field. This chapter 3 explains how to gather the data and methods use. Data will be gathered by interviews and questionaire. It show the context and access; where, when, and how the researcher getting the information and data analysis. Next is Chapter 4 where the case study begun. In this chapter, the researcher will elaborate on her case study where she manage to find. The researcher has choose MRT Sungai Buloh-Kajang Line and Tetuan Platinum Victory Sdn Bhd as her case study in order to complete the research. However, the finding will be discuss in the next chapter in tabulation of data. The analysis will be shown in chart form whether it is in bar chart or pie chart.